1997
DOI: 10.1074/jbc.272.32.19858
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptors α and β Form Heterodimers on DNA

Abstract: The estrogen receptor (ER) is expressed in two forms, ER␣ and ER␤. Here we show that ER␣ and ER␤, expressed both in vitro and in vivo, form heterodimers which bind to DNA with an affinity (K d of approximately 2 nM) similar to that of ER␣ and greater than that of ER␤ homodimers. Mutation analysis of the hormone binding domain of ER␣ suggests that the dimerization interface required to form heterodimers with ER␤ is very similar but not identical to that required for homodimer formation. The heterodimer, like th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
348
2
12

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 623 publications
(380 citation statements)
references
References 30 publications
18
348
2
12
Order By: Relevance
“…Moreover, it has been reported that the ER-α protein and the ER-β mRNA are co-localized in neurons in the rat brain (Shughrue et al, 1998;Orikasa et al, 2002), and the activity of estrogenic compounds may depend, in part, on whether a cell contains ER-α, β, or both. In addition, it is known that ERs form homo-or heterodimers (Cowley et al, 1997;Pace et al, 1997;Pettersson et al, 1997;Ogawa et al, 1998;Matsuda et al, 2002). There is a possibility that estrogen demonstrates different physiological actions via homo-or heterodimers, and the formation of dimers may be affected by decreased levels of ER-β in the specific brain regions in which decreases were observed in aged female rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been reported that the ER-α protein and the ER-β mRNA are co-localized in neurons in the rat brain (Shughrue et al, 1998;Orikasa et al, 2002), and the activity of estrogenic compounds may depend, in part, on whether a cell contains ER-α, β, or both. In addition, it is known that ERs form homo-or heterodimers (Cowley et al, 1997;Pace et al, 1997;Pettersson et al, 1997;Ogawa et al, 1998;Matsuda et al, 2002). There is a possibility that estrogen demonstrates different physiological actions via homo-or heterodimers, and the formation of dimers may be affected by decreased levels of ER-β in the specific brain regions in which decreases were observed in aged female rats.…”
Section: Discussionmentioning
confidence: 99%
“…ER-β mRNA was shown to be co-expressed with ER-α immunoreactivity in the same neuron in several brain regions: the bed nucleus of the stria terminalis, medial amygdaloid nucleus, periventricular preoptic nucleus, medial preoptic nucleus, and anteroventral periventricular nucleus (Shughrue et al, 1998;Orikasa et al, 2002). In addition, in vitro studies have shown that ER-β can form heterodimers with ER-α (Cowley et al, 1997;Pace et al, 1997;Pettersson et al, 1997;Ogawa et al, 1998;Matsuda et al, 2002), 5 suggesting that estrogen may differentially modulate the activity of certain neuronal populations depending on whether the cells express ER-α, ER-β or both (Shughrue et al, 1998). ER-β mRNA is also highly distributed in several rat brain regions, including the olfactory bulb, cerebral cortex, paraventricular hypothalamic nucleus, supraoptic nucleus, hippocampus and cerebellar Purkinje cells, areas that contain little or no ER-α mRNA (Simerly et al, 1990;Shughrue et al, 1997;Mufson et al, 1999;Shima et al, 2003;Mehra et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…ERα and ERβ preferentially form functional heterodimers that bind DNA with an affinity similar to that of ERα homodimers, and greater than that of ERβ homodimers [34]. Many cellbased studies suggest that ERβ acts as a negative modulator of ERα action.…”
Section: B Influence Of Erβ On Erα Actions: Novel Activity Of Heteromentioning
confidence: 99%
“…Functionally both receptors share several characteristics in that they bind estradiol (E 2 ) and related compounds and recognize and initiate transcription from palindromic DNA sequences referred to as estrogen response elements (ERE) (Kuiper et al, 1996). ERb has been reported to have weaker transcriptional activity in response to E 2 compared to ERa in transient co-transfection assays in several cell systems (Cowley et al, 1997;Pettersson et al, 1997;Watanabe et al, 1997). ERb also, in contrast to ERa, fails to show agonistic response to the well known anti-estrogen tamoxifen (Tremblay et al, 1997;Watanabe et al, 1997).…”
Section: Introductionmentioning
confidence: 99%